2022
DOI: 10.1371/journal.pcbi.1009397
|View full text |Cite
|
Sign up to set email alerts
|

Metaproteomics as a tool for studying the protein landscape of human-gut bacterial species

Abstract: Host-microbiome interactions and the microbial community have broad impact in human health and diseases. Most microbiome based studies are performed at the genome level based on next-generation sequencing techniques, but metaproteomics is emerging as a powerful technique to study microbiome functional activity by characterizing the complex and dynamic composition of microbial proteins. We conducted a large-scale survey of human gut microbiome metaproteomic data to identify generalist species that are ubiquitou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…To overcome these boundaries, mass spectrometry-based proteomics applied to the study of hundreds of microbial organisms (termed, metaproteomics ( Rodriguez-Valera, 2004 ; Wilmes and Bond, 2004 )) has emerged as an attractive alternative. Metaproteomics has the potential to understand complex host-microbiome interactions as it enables the analysis of entire sets of proteins, providing direct insights into the identity and functionality of microorganisms present in an ecosystem ( Stamboulian et al, 2022 ). However, proteomics acquisition methods classically used in metaproteomics have reached their theoretical profiling limits ( Duan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these boundaries, mass spectrometry-based proteomics applied to the study of hundreds of microbial organisms (termed, metaproteomics ( Rodriguez-Valera, 2004 ; Wilmes and Bond, 2004 )) has emerged as an attractive alternative. Metaproteomics has the potential to understand complex host-microbiome interactions as it enables the analysis of entire sets of proteins, providing direct insights into the identity and functionality of microorganisms present in an ecosystem ( Stamboulian et al, 2022 ). However, proteomics acquisition methods classically used in metaproteomics have reached their theoretical profiling limits ( Duan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fecal metaproteomic, as an emerging multi-omics technology, is a powerful tool for identifying previously unknown microbial communities and understanding the function of the gut microbiota [ 42 , 43 ]. A recent fecal metaproteomic report from Germany described negative associations between transcriptional regulatory protein RprY and human IgA from Bacillus fragilis and IBD.…”
Section: Discussionmentioning
confidence: 99%
“…P. vulgatus is one of the commonly found bacterial species in human microbiome. In previous work, we showed that P. vulgatus is one of the generalists that are found in gut microbiomes of healthy individuals and individuals with diseases using metaproteomics datasets ( Stamboulian et al., 2022 ). This served as motivation to include P. vulgatus in our current study.…”
Section: Methodsmentioning
confidence: 99%